Sistem Monitoring Suhu dan Kelembaban Berbasis Internet of Things (IoT) Pada Ruang Data Center - Kusumah, Rafik; Islam, Hajar Izzatul; Sobur, Susilawati (Journal of Applied Informatics and Computing, 2023)
The Internet of Things (IoT) has brought significant advancements in various fields, including environmental monitoring. This study presents the implementation of an IoT-based temperature and humidity monitoring system specifically designed for a data center. The monitoring device consists of a DHT11 sensor, water level sensor, OLED I2C display, and ESP8266 (NodeMCU) microcontroller, enabling accurate and consistent measurements of temperature and humidity levels. Through extensive hardware testing, the developed device has demonstrated its effectiveness in accurately measuring temperature and humidity within the data center. Comparative analysis of the hardware data with readings from the HTC-2 device revealed minimal error rates, with an average of 1.7% for temperature and 2.1% for humidity, affirming the reliability and consistent performance of this device. Software testing showcased the monitoring application's efficiency in displaying temperature and humidity data through an intuitive dashboard. Users can easily access real-time data and statistical graphs, facilitating effective monitoring and analysis of the environmental conditions in the data center.